2017
DOI: 10.5430/afr.v6n3p153
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Factors Affecting the Choice of Investment Portfolio by Individual Investors in Singapore

Abstract: Singapore being an island economy and a financial hub with residents from diverse backgrounds, huge ethnic diversity, coming from different part of the world. This study aims to gain insights and information into the factors that affect investment planners, financial advisers and individuals need to consider improving their choice of the portfolio and its performance. People’s investment decisions and hence their portfolio, which hitherto has not been tested. Furthermore, it intends to identify the factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
2
16
1
1
Order By: Relevance
“…The research was supported by further research, namely Sindhu & Kumar (2014), Farayibi (2015), Malik (2017), who found the same results. This study contradicts the research from, Seetharaman et al (2017) huge ethnic diversity, coming from different part of the world. This study aims to gain insights and information into the factors that affect investment planners, financial advisers and individuals need to consider improving their choice of the portfolio and its performance.…”
Section: Effect Of Risk On Investment Interestcontrasting
confidence: 83%
“…The research was supported by further research, namely Sindhu & Kumar (2014), Farayibi (2015), Malik (2017), who found the same results. This study contradicts the research from, Seetharaman et al (2017) huge ethnic diversity, coming from different part of the world. This study aims to gain insights and information into the factors that affect investment planners, financial advisers and individuals need to consider improving their choice of the portfolio and its performance.…”
Section: Effect Of Risk On Investment Interestcontrasting
confidence: 83%
“…The results of much research confirm the impact of many different socio-demographic factors, for instance: age, education, income, wealth, employment status and occupation, stages in the life cycle and marital status (Aren & Aydemir, 2015;Barasinska & Schäfer, 2018;Kumari, Satya, & Kritika, 2018). The conducted research also confirms that an investment objective and an asset familiarity play a vital role in the choice of elements of the investment portfolio (Seetharaman, Niranjan, Patwa, & Kejriwal, 2017). After the financial crisis, the literature more and more often refers to an additional category of factors, namely psychographic variables (Geetha & Vimala, 2014;Kiran & Rao, 2005), personality traits, behavioural biases, sentiment and others, like social interactions and media (Goodfellow & Gebka, 2009;Kourtidis, Sevic, & Chatzoglou, 2011;Nguyen & Bhatti, 2015).…”
Section: Literature Reviewsupporting
confidence: 60%
“…For example, discrete choice modeling (DCM; Louviere et al 2000) has been applied to understand the impact of revenue management and loyalty program attributes on travelers' purchasing choices (Mathies et al 2013), of value creation and value appropriation attributes on managers' outsourcing choices (Lin et al 2016) and of location attributes on foreign direct investment choices (Buckley et al 2007). Then, as one of the alternative approaches, partial least squares structural equation modeling (PLS-SEM;Lohmöller 1989;Sarstedt et al 2017a;Wold 1982) has been employed to explain and predict the impact of attributes such as expected return and asset familiarity on choice of investment portfolio (Seetharaman et al 2017), ease of use and trustworthiness on intentions to use consumer-generated media for travel planning (Ayeh et al 2013) and price and convenience on, ultimately, intentions to purchase travel online (Amaro and Duarte 2015). Notwithstanding other analytical approaches, DCM, however, remains the commonly referred to analytical approach to explain discrete choices.…”
Section: Introductionmentioning
confidence: 99%